Treating Metastatic Brain Cancers With Stem Cells - Sadanandan, Nadia; Shear, Alex; Brooks, Beverly; Saft, Madeline; Cabantan, Dorothy Anne Galang; Kingsbury, Chase; Zhang, Henry; Anthony, Stefan; Wang, Zhen-Jie; Salazar, Felipe Esparza; Lezama Toledo, Alma R.; Rivera Monroy, Germán; et al. (Frontiers in Molecular Neuroscience, 2021)
Stem cell therapy may present an effective treatment for metastatic brain cancer and glioblastoma. Here we posit the critical role of a leaky blood-brain barrier (BBB) as a key element for the development of brain metastases, specifically melanoma. By reviewing the immunological and inflammatory responses associated with BBB damage secondary to tumoral activity, we identify the involvement of this pathological process in the growth and formation of metastatic brain cancers. Likewise, we evaluate the hypothesis of regenerating impaired endothelial cells of the BBB and alleviating the damaged neurovascular unit to attenuate brain metastasis, using the endothelial progenitor cell (EPC) phenotype of bone marrow-derived mesenchymal stem cells. Specifically, there is a need to evaluate the efficacy for stem cell therapy to repair disruptions in the BBB and reduce inflammation in the brain, thereby causing attenuation of metastatic brain cancers. To establish the viability of stem cell therapy for the prevention and treatment of metastatic brain tumors, it is crucial to demonstrate BBB repair through augmentation of vasculogenesis and angiogenesis. BBB disruption is strongly linked to metastatic melanoma, worsens neuroinflammation during metastasis, and negatively influences the prognosis of metastatic brain cancer. Using stem cell therapy to interrupt inflammation secondary to this leaky BBB represents a paradigm-shifting approach for brain cancer treatment. In this review article, we critically assess the advantages and disadvantages of using stem cell therapy for brain metastases and glioblastoma.